Development and validation of a clinical index to predict survival after cardiac resynchronisation therapy. Issue 19 (9th July 2009) - Leyva, F; Foley, P W X; Stegemann, B; Ward, J A; Ng, L L; Frenneaux, M P; Regoli, F; Smith, R E A; Auricchio, A
Abstract : Objective: To develop and validate a prognostic risk index of cardiovascular mortality after cardiac resynchronisation therapy (CRT). Design: Prospective cohort study. Setting: District general hospital. Patients: 148 patients with heart failure (mean age 66.7 (SD 10.4) years), New York Heart Association class III or IV, LVEF <35%) who underwent CRT. Interventions: CRT device implantation. Main outcome measures: Value of a composite index in predicting cardiovascular mortality, validated internally by bootstrapping. The predictive value of the index was compared to factors that are known to predict mortality in patients with heart failure. Results: All patients underwent assessment of 16 prognostic risk factors, including cardiovascular magnetic resonance (CMR) measures of myocardial scarring (gadolinium-hyperenhancement) and dyssynchrony, before implantation. Clinical events were assessed after a median follow-up of 913 (interquartile range 967) days. At follow-up, 37/148 (25%) of patients died from cardiovascular causes. In Cox proportional hazards analyses, (DSC) Dyssynchrony, posterolateral Scar location (both p<0.0001) and Creatinine (p = 0.0046) emerged as independent predictors of cardiovascular mortality. The DSC index, derived from these variables combined, emerged as a powerful predictor of cardiovascular mortality. Compared to patients with a DSC <3, cardiovascular mortality in patients in the intermediate DSC index (3–5; HR: 11.1 (95% confidence interval (CI) 3.00 to 41.1), p = 0.0003) and high DSC index (⩾5; HR: 30.5 (95% CI 9.15 to 101.8), p<0.0001) were higher. Bootstrap validation confirmed excellent calibration and internal validity of the prediction model. Conclusion: The DSC index, derived from a standard CMR scan and plasma creatinine before implantation, is a powerful predictor of cardiovascular mortality after CRT.